Moral and Contextual Dimensions of “Inappropriate” Antibiotic Prescribing in Secondary Care: A Three-Country Interview Study - Tarrant, Carolyn; Krockow, Eva M.; Nakkawita, W. M. I. Dilini; Bolscher, Michele; Colman, Andrew M.; Chattoe-Brown, Edmund; Perera, Nelun; Mehtar, Shaheen; Jenkins, David R. (Frontiers in Sociology, 2020)
Abstract Overuse of broad-spectrum antibiotics in secondary care is a key contributor to the emergence and spread of antimicrobial resistance (AMR); efforts are focused on minimising antibiotic overuse as a crucial step towards containing the global threat of AMR. The concept of overtreatment has, however, been difficult to define. Efforts to address the overuse of medicine need to be informed by an understanding of how prescribers themselves understand the problem. We report findings from a qualitative interview study of 46 acute care hospital prescribers differing in seniority from three countries: United Kingdom, Sri Lanka and South Africa. Prescribers were asked about their understanding of inappropriate use of antibiotics. Prescriber definitions of inappropriate use included relatively clear-cut and unambiguous cases of antibiotics being used “incorrectly” (e.g., in the case of viral infections). In many cases, however, antibiotic prescribing decisions were seen as involving uncertainty, with prescribers having to make decisions about the threshold for appropriate use. Decisions about thresholds were commonly framed in moral terms. Some prescribers drew on arguments about their duty to protect public health through having a high threshold for prescribing, while others made strong arguments for prioritising risk avoidance for the patients in front of them, even at a cost of increased resistance. Notions of whether prescribing was inappropriate were also contextually dependent: high levels of antibiotic prescribing could be seen as a rational response when prescribers were working in challenging contexts, and could be justified in relation to financial and social considerations. Inappropriate antibiotic use is framed by prescribers not just in clinical, but also in moral and contextual terms; this has implications for the design and implementation of antibiotic stewardship interventions aiming to reduce inappropriate use of antibiotics globally.